An optimization-based approach to assess non-interference in labeled and bounded Petri net systems. (May 2022) - Basile, Francesco; Boccia, Maurizio; De Tommasi, Gianmaria; Motta, Carlo; Sterle, Claudio
Abstract: An optimization-based approach to assess both strong non-deterministic non- interference (SNNI) and bisimulation SNNI (BSNNI) in discrete event systems modeled as labeled Petri nets is presented in this paper. The assessment of SNNI requires the solution of feasibility problems with integer variables and linear constraints, which is derived by extending a previous result given in the case of unlabeled net systems. Moreover, the BSNNI case can be addressed in two different ways. First, similarly to the case of SNNI, a condition to assess BSNNI, which is necessary and sufficient, can be derived from the one given in the unlabeled framework, requiring the solution of feasibility problems with integer variables and linear constraints. Then, a novel necessary and sufficient condition to assess BSNNI is given, which requires the solution of integer feasibility problems with nonlinear constraints. Furthermore, we show how to recast these problems into equivalent mixed-integer linear programming (MILP) ones. The effectiveness of the proposed approaches is shown by means of several examples. It turns out that there are relevant cases where the new condition to assess BSNNI that requires the solution of MILP problems is computationally more efficient, when compared to the one that requires the solution of feasibility problems.